Demand for Green Skills in an Evolving Landscape - Esther Arenas-Arroyo; Jacob Fabian; Friederike Mengel; Bernhard Schmidpeter; Michel Serafinelli (Institute of Labor Economics (IZA), 2025)
How does firms' skill demand change as the business landscape evolves? We present evidence from the green transition by analyzing how hurricanes impact demand for green skills. These disasters signal the risks of not acting on environmental issues. Using data from U.S. online job postings (2010–2019) and hurricane paths, we create a new measure of green job postings. Firms in areas affected by hurricanes are 6.4% more likely to post jobs that require green skills after the event, particularly those serving local markets.
Keywords: J23; Q54; L20; J24; 330; green skills; green transition; online job postings; hurricanes